2009
DOI: 10.1002/qj.392
|View full text |Cite
|
Sign up to set email alerts
|

A weak‐constraint four‐dimensional variational analysis system in the stratosphere

Abstract: A weak-constraint four-dimensional variational (4D-Var) analysis system designed to correct stratospheric model errors has been evaluated. Verifications against upper-level radiosonde temperature observations and Stratospheric Sounding Unit (SSU) radiance data show that the addition of a weak constraint in the stratosphere can greatly reduce analysis bias. Both single-observation analysis experiments and extended assimilations have been performed to help us understand the impact of the model error covariance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The result that 12 h variances are a few percent more balanced than 3 h variances and that the large-scale balanced variance gained during 9 h forecast is mainly in the balanced and Kelvin modes may be at least partially related to the largescale noise in the input forecast differences. This explanation is supported by the results of Lindskog et al (2009), who found that analysis increments in the stratosphere are noisy. Fisher et al (2009) discuss two possible reasons for the noisy ensemble differences.…”
Section: Discussionsupporting
confidence: 55%
“…The result that 12 h variances are a few percent more balanced than 3 h variances and that the large-scale balanced variance gained during 9 h forecast is mainly in the balanced and Kelvin modes may be at least partially related to the largescale noise in the input forecast differences. This explanation is supported by the results of Lindskog et al (2009), who found that analysis increments in the stratosphere are noisy. Fisher et al (2009) discuss two possible reasons for the noisy ensemble differences.…”
Section: Discussionsupporting
confidence: 55%
“…The alternating positive/negative anomalies in the temperature vertical structure in high latitudes, visible particularly in the stratosphere, are similar to deficiencies in analyses and increments reported previously concerning other datasets (Uppala et al, 2005;Tremolet, 2007;Lindskog et al, 2009). By contrast, these authors used time-invariant, regressionbased constraints, which indicates that the issue is generic and not related to flow dependence.…”
Section: Validation Of Solution Proceduresmentioning
confidence: 49%
“…The work of [80] illustrated the implementation of weak-constraint 4D-Var using such a matrix, again in the ECMWF system, to estimate a constant bias error in the stratosphere, where the model is known to have biases. A similar scheme has been introduced into the operational assimilation system of ECMWF [40].…”
Section: Weak Constraint Variational Assimilationmentioning
confidence: 99%